1984
DOI: 10.1002/jmv.1890140206
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus shedding by newborn children

Abstract: We studied the shedding of rotavirus by newborn children in the nurseries of a large maternity hospital in Caracas, Venezuela, throughout the year 1982. Sixty-two (57%) of 108 children examined shed the virus within the first few days of life. Four (6%) of the 62 children who shed rotavirus had diarrhea but only one of them required oral rehydration therapy. The rotavirus specimens were identified as subgroup 2 in an ELISA subgrouping assay that employs monoclonal antibodies. Analysis of the RNA extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1
1

Year Published

1985
1985
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 24 publications
2
41
1
1
Order By: Relevance
“…The occurrence of a single rotavirus strain in the neonatal unit and its persistence over long periods of time have also been reported [Perez-Schael et al, 1984;Rodger et al, 1981;Steele and Alexander, 19871. The apparent genomic stability and persistence of a single strain of rotavirus in neonatal units is in stark contrast to the genomic variability that is seen in older infant populations infected with (%I 1992 WILEY-LISS, INC.…”
Section: Introductionmentioning
confidence: 81%
“…The occurrence of a single rotavirus strain in the neonatal unit and its persistence over long periods of time have also been reported [Perez-Schael et al, 1984;Rodger et al, 1981;Steele and Alexander, 19871. The apparent genomic stability and persistence of a single strain of rotavirus in neonatal units is in stark contrast to the genomic variability that is seen in older infant populations infected with (%I 1992 WILEY-LISS, INC.…”
Section: Introductionmentioning
confidence: 81%
“…Neonatal infection with rotavirus has been reported as a common phenomenon in British, Australian, and Venezuelan maternity hospitals [15][16][17]. Such infection is probably nosocomial, with house staff acting as the main disseminators.…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus infections are more likely to be severe in children 3 to 24 months of age than in younger infants or older children and adults (21,67,88) Longitudinal studies demonstrated that naturally acquired rotavirus infections provide protection against rotavirus disease upon reinfection and that protection is greatest against the most severe disease outcomes (29,80) Although children can be infected with rotavirus several times during their lives, initial infection after 3 months of age is most likely to cause severe diarrhea and dehydration.…”
Section: Natural Protectionmentioning
confidence: 99%